2015
DOI: 10.1021/acsphotonics.5b00281
|View full text |Cite
|
Sign up to set email alerts
|

Optical Plasmons of Individual Gold Nanosponges

Abstract: The search for novel plasmonic nanostructures, which can act simultaneously as optical detectors and stimulators, is crucial for many applications in the fields of biosensing, electro- and photocatalysis, electrochemistry, and biofuel generation. In most of these areas, a large surface-to-volume ratio, as well as high density of active surface sites, is desirable. We investigate sponge-like, that is, fully porous, nanoparticles, called nanosponges, where both the gold and the air phase are fully percolated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 36 publications
6
78
0
Order By: Relevance
“…In order to get a more deeper insight on the optical behavior and properties experimentally, Vidal et al have perfomred the measurements of single particle order single nanosponge spectroscopy, and revealed that the optical properties of the individual nanosponges are much more complicated than those of their solid conterparts [22]. The plasmon renonance of the individual gold nanosponges with similar form, size, porosity, and ligament/ pore size differs notably from each other.…”
Section: Multiple Plasmon Resonances and Polarization Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…In order to get a more deeper insight on the optical behavior and properties experimentally, Vidal et al have perfomred the measurements of single particle order single nanosponge spectroscopy, and revealed that the optical properties of the individual nanosponges are much more complicated than those of their solid conterparts [22]. The plasmon renonance of the individual gold nanosponges with similar form, size, porosity, and ligament/ pore size differs notably from each other.…”
Section: Multiple Plasmon Resonances and Polarization Dependencementioning
confidence: 99%
“…Furthermore, the gold nanosponges demonstrate an interesting and strong polarization effect [22,23]. Figure 7 shows the SEM images of two individual gold nanosponges and the corresponding polarization-dependent scattering spectra.…”
Section: Multiple Plasmon Resonances and Polarization Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…were fabricated and tested as versatile SERS substrates [12][13][14][15][16][17][18][19][20][21][22][23] . Specifically, porous materials, nanostructures and nanoparticles, routinely reaching uniform SERS enhancement sufficient to overcome single-molecule detection limit independently on excitation/detection conditions, are of growing interest [24][25][26] .…”
mentioning
confidence: 99%
“…High surface-to-volume ratio coupled with multiple plasmon resonances in the visible or near-infrared (NIR) range is critical for surface-enhanced Raman scattering (SERS) [112] or IR spectroscopy (SEIRA) [113]. Despite the diminished crosssection that dampens plasmon resonance in nanoparticles with diameters below 15 nm [114], more complicated structures such as nanostars [115] or nanosponges [116] create large scattering cross-sections, as well as further enhanced surface-to-volume ratio.…”
Section: Organic 1d Semiconductor Systemsmentioning
confidence: 99%